The pea ferredoxin I gene exhibits different light responses in pea and tobacco. - Gallo-Meagher, M (1992)
We monitored Fed-1 (encoding ferredoxin I) mRNA levels in etiolated transgenic tobacco seedlings containing the intact pea Fed-1 gene to determine if the characteristic light responses of this gene in pea seedlings are also observed in transgenic tobacco. Fed-1 transcript levels in transgenic tobacco seedlings closely paralleled those of the native gene in pea buds when etiolated seedlings were transferred to white light. However, the response to red light was much smaller in tobacco than in pea and was not efficiently reversed by far-red light. The red light response of endogenous tobacco ferredoxin transcripts is closely comparable to that of the Fed-1 transgene, with a similar lack of photoreversibility. Thus, the pea Fed-1 transgene responds normally to tobacco gene-regulatory factors, but these factors are less influenced by phytochrome in tobacco cotyledons than in pea buds.